FEATURES OF RELIGIOUS FOOD IN CATERING SERVICES (Development Service Industry Management, 2025)
The article examines the organization of food in accordance with the religious preferences of each guest during catering services. The organization of food in accordance with the fasting restrictions established in the Christian tradition is considered. It is recommended to exclude meat, dairy products, eggs, as well as sweets based on ingredients of animal origin. Instead, we suggest using cereals, vegetables, fruits, mushrooms, nuts and other plant products, applying a creative approach to serving and flavoring solutions. Clear labeling of dishes according to the client's wishes should be mandatory. The principles of nutrition according to Islamic traditions (halal) are studied and a strict ban on pork, alcohol and potentially ritually unclean products is noted. Catering companies are recommended to cooperate with certified suppliers, equip separate kitchen areas for preparing halal dishes and ensure that staff are aware of the relevant standards. The service of Hindus in the field of catering services is considered. The importance of excluding beef is emphasized and suggestions are made for a full vegetarian menu based on legumes, rice, vegetables, spices and dairy products, without the use of eggs. The service of Buddhists is characterized, where food is perceived as a source of energy, harmony and internal balance. It is noted that Buddhists adhere to a vegetarian or vegan diet, avoiding all products of animal origin. It is recommended to prepare dishes with a minimum amount of spices, focusing on simplicity, naturalness and balance of flavors, using cereals, legumes, vegetables and fruits. It is concluded that religious nutrition requires from the catering company not only culinary skills, but also ethical responsibility, adaptability and a deep understanding of intercultural characteristics.
Keywords: religious food; catering; service